Survei Sarana Dan Prasarana Pendidikan Jasmani Sekolah Menengah Pertama Negeri Di Kabupaten Grobogan Tahun 2020 (Indonesian Journal for Physical Education and Sport, 2021)
The purpose of this study was to determine the physical education facilities and infrastructure of State Junior High Schools in Grobogan Regency. This research used quantitative research methods. This reseacrh was a survey research. The variables of this study were physical education facilities and infrastructure. The research population questionnaire was taken from 10 State Junior High Schools in Grobogan Regency. The sample used saturated sampling and the sampling used the quota sampling technique. The subjects in this study were physical education teachers of State Junior High Schools in Grobogan Regency. The data analysis technique used descriptive analysis, the method analysis used quantitative descriptive analisis by classifying the types of data obtained from the observation sheet and grouped. The results of the research that have been conducted indicate that the state of the existing facilities and infrastructure of Junior High School in Grobogan Regency is still limited.